PENGEMBANGAN MEDIA LIFT THE FLAP BOOK PADA PEMBELAJARAN TEMATIK TEMA 8 LINGKUNGAN SAHABAT KITA KELAS V SD - May Liavani; Beta Rapita Silalahi (Melati Institute, 2023)
This study aims to: (1) develop lift the flap book media in the thematic learning theme 8 Our Friendly Environments class V SD, (2) determine the feasibility of lift the flap book media in the thematic learning theme 8 Our Friendly Environment class V SD. This research is a type of research and development (Research and Development) using the ADDIE development model which consists of 5 stages, namely Analysis , Design , Development , Implementation , and Evaluation. The instruments used to collect data were media expert questionnaires, material expert questionnaires and student response questionnaires. The data analysis technique is a qualitative and quantitative descriptive analysis technique. Based on the validation results from media experts, an average percentage of 95% was obtained in the